2015
DOI: 10.1016/j.socscimed.2015.09.029
|View full text |Cite
|
Sign up to set email alerts
|

Does a college education reduce depressive symptoms in American young adults?

Abstract: Higher levels of educational attainment are consistently associated with better mental health. Whether this association represents an effect of education on mental health, however, is less clear as omitted variable bias remains a pressing concern with education potentially serving as a proxy for unobserved factors including family background and genetics. To combat this threat and come closer to a causal estimate of the effect of education on depressive symptoms, this study uses data on 231 monozygotic twin pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
38
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 55 publications
(75 reference statements)
8
38
4
Order By: Relevance
“…Thirdly, the interaction effect of education on the relationship between childhood neighborhood qualities was not found in this study. This is counter to most previous studies [37,51]. The reason may be explained by: previous study was examined among young adulthood [37], while our study was conduct among old adult.…”
Section: Discussioncontrasting
confidence: 65%
See 2 more Smart Citations
“…Thirdly, the interaction effect of education on the relationship between childhood neighborhood qualities was not found in this study. This is counter to most previous studies [37,51]. The reason may be explained by: previous study was examined among young adulthood [37], while our study was conduct among old adult.…”
Section: Discussioncontrasting
confidence: 65%
“…This is counter to most previous studies [37,51]. The reason may be explained by: previous study was examined among young adulthood [37], while our study was conduct among old adult. Due to no chance or low chance to get high education before 1977s in China, more than 91.44% of participant graduated from primary school or below.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…Being married was associated with lower odds of membership in a trajectory group with higher depression score. The result that higher educational level was associated with higher depression scores contradicts a large body of research in general populations indicating the opposite (Erickson et al, 2016;Lorant et al, 2003;McFarland & Wagner, 2015;Miech & Shanahan, 2000;Peyrot et al, 2015). Some studies have, however, not been able to confirm such an association (Inaba et al, 2005), and it has been pointed out that results vary depending on for example region and the way depression is measured (Lorant et al, 2003).…”
Section: Discussionmentioning
confidence: 88%
“…The twin design accounts for shared family background and confounding genetic factors, which may otherwise cause omitted variable bias. Based on twin data, McFarland and Wagner (2015) and Mezuk et al (2013) found that higher education was related to lower levels of depressive symptoms. Fujiwara and Kawachi (2009), who also use twin design, however, did not find such a relationship.…”
Section: Accepted Manuscriptmentioning
confidence: 99%